2021
DOI: 10.3389/fpsyg.2021.785004
|View full text |Cite
|
Sign up to set email alerts
|

Narrative and Bodily Identity in Eating Disorders: Toward an Integrated Theoretical-Clinical Approach

Abstract: Eating disorders (EDs) can be viewed as “embodied acts” that help to cope with internal and external demands that are perceived as overwhelming. The maintenance of EDs affects the entire identity of the person; the lack of a defined; or valid sense of self is expressed in terms of both physical body and personal identity. According to attachment theory, primary relationships characterized by insecurity, traumatic experiences, poor mirroring, and emotional attunement lead to the development of dysfunctional reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Specifically, attachment insecurity has a prevalence ranging from 70% in eating disorder patients [ 45 , 46 ] to 95% [ 47 ] and 100% [ 48 ]; it has also been considered an important risk factor for the occurrence of dysfunctional eating behaviors in the nonclinical population [ 19 , 49 ]. Traumatic life experiences, especially when experienced early and repeatedly over time, considerably increase this risk and play a major role in both the development and maintenance of dysfunctional circuits [ 50 ]. These experiences are rooted in the childhood strategies of insecure attachment (avoidant pattern (A), ambivalent pattern (C), and disorganized pattern (D)) and then in adult SoM (dismissing (DS), entangled (E), unresolved (U), or cannot classify (CC)) [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, attachment insecurity has a prevalence ranging from 70% in eating disorder patients [ 45 , 46 ] to 95% [ 47 ] and 100% [ 48 ]; it has also been considered an important risk factor for the occurrence of dysfunctional eating behaviors in the nonclinical population [ 19 , 49 ]. Traumatic life experiences, especially when experienced early and repeatedly over time, considerably increase this risk and play a major role in both the development and maintenance of dysfunctional circuits [ 50 ]. These experiences are rooted in the childhood strategies of insecure attachment (avoidant pattern (A), ambivalent pattern (C), and disorganized pattern (D)) and then in adult SoM (dismissing (DS), entangled (E), unresolved (U), or cannot classify (CC)) [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, examining the attachment dynamics in the life histories of ED patients and understanding the quality of their SoM are essential activities in the clinical setting, not only for the formulation of a diagnostic hypothesis but also to elucidate useful information with respect to what these aspects of the individual’s functioning suggest about the therapeutic relationship, the outcome of treatment, the possible responses to separations during the therapeutic process, and the risk of dropping out [ 50 , 83 , 84 ]. Knowledge of the regulatory systems for coping with vulnerability learned in childhood, in interaction with attachment figures, makes it possible to maintain an attitude of emotional closeness appropriate to the patient, in addition to aiding in development of the therapeutic relationship and helping the patient develop new strategies to cope with stressful situations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on clinical reports and a narrative review of the literature, it has been observed that patients with ED experience a distortion between their perceived body image and schema and their actual reality (Thurm, 2012; Miller, 1991; Longo & Haggard, 2012; Pellegrini et al, 2021; Riva, 2014). Consequently, individuals with ED exhibit a significantly stronger response to the rubber hand illusion, both in terms of perceptual (proprioceptive bias) and subjective (self-report) measures, compared to healthy controls (Eshkevari et al, 2014).…”
Section: Self-awareness In Eating Disordersmentioning
confidence: 99%
“…Consequently, the formation and organization of our body image are integral aspects of our overall identity. From this perspective, the maintenance of an ED directly affects the subject’s identity (Pellegrini et al, 2021; Longo & Haggard, 2012). In line with self-objectification theory, which posits that individuals come to view themselves as objects to be evaluated based on appearance, the maintenance of an ED can exacerbate this tendency (Fredrickson & Roberts, 1997).…”
Section: Self-awareness In Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation